Acute gastroduodenal ulcer - C. Castiglioni, Juan; C. Camaño, Mario; C. Pradines, Jorge (Cirugía del Uruguay, 1971)
Seven cases of acute gastroduodenal ulcer are discussed, with considerations of its ethiology, pathogenesis and clinics. The different possibilities for its surgical treatment are analyzed.